Improvement of the organizational and economic mechanism for the formation of environmentally safe land use - Kupriianchyk, I. (Land Management, Cadastre and Land Monitoring, 2023)
The organizational and economic mechanism of ecologically safe land use is an effective tool for the interest of landowners and land users in compliance with the requirements of environmental standards. The use of such a mechanism contributes to the effective management of land resources at various levels.The article proposes an improved structure of the organizational and economic mechanism for the formation of ecologically safe agrarian land use. Given the specifics of land use, two more instrumental blocks of a cross-functional nature, namely: regulatory and land management, are allocated at the same level as the organizational and economic blocks.For each of the named instrumental blocks, specific tools are defined that allow to ensure the formation of ecologically safe land use.It has been established that any organizational and economic mechanism, in a broad sense, is a certain set of action tools and the necessary forms, methods and levers of their functioning, while simultaneously understanding the mechanism exclusively as a set of tools. Implementation of the developed organizational mechanism for the formation of ecologically safe agrarian land use is carried out by improving the structural scheme, the essence and toolkit of which is transformed depending on the tasks and functions of the main instrumental blocks.It is justified that all four instrumental blocks should be based on consideration of four dimensions: legal, spatial, ecological and social.Keywords. Ecologically safe land use, organizational and economic mechanism, ecological safety, agricultural lands.
Keywords: еcologically safe land use; organizational and economic mechanism; ecological safety; agricultural lands.